MULTILATERAL DIPLOMACY: DISSENTS AND CONTRASTS. TWO GENEBRINE CASES, A PERSONAL TESTIMONY - Coelho, Pedro Motta Pinto (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
In the multilateral negotiating context in Geneva, developed countries seek, often aggressively, to impose agendas that are more favorable to their interests. This text seeks to expose, from the perspective of developing countries, and Brazil in particular, the difficulties inherent in multilateral work at the time they were experienced, as well as the efforts to overcome them. The focus of attention is modulated, sometimes focusing on the GATT (institution that preceded the WTO) and the negotiations on the new themes of the Uruguay Round of trade negotiations (1986-1994), now on the nascent diplomatic articulations on the issue of the environment; or even in the negotiations on disarmament, these at a more recent moment, with the conclusion of the Treaty on the Prohibition of Nuclear Weapons.